Refugee Benefit Cuts - Christian Dustmann; Rasmus Landerso; Lars Højsgaard Andersen (Institute of Labor Economics (IZA), 2023)
This paper analyzes the effects of Denmark's Start Aid welfare reform that targets refugees. Implemented in 2002, it enables us to study not only the reform's immediate effects, but also its longerterm consequences, and its repeal a decade later. The reform-induced large transfer cuts led to an increase in employment rates, but only in the short run. Overall, the reform increased poverty rates and led to a rise in subsistence crime. Moreover, local demand conditions generate substantial heterogeneity in the reform's effects on immediate and longer-term employment.
Keywords: E64; I30; J60; 330; labor market outcomes; welfare state; social assistance; labor demand; migration